په‌یوه‌ندى خێزان به‌ بونیادنانى تواناكانى خوێندكار توێژینه‌وه‌یه‌كى مه‌يدانیه‌ له‌ ئاماده‌ییه‌كانى شارى سلێمانى (مستل) - حسین, كه‌ژاڵ عه‌لى; زۆراب, دارا ئه‌نوه‌ر (Sulaimani Journal for Humanities, 2022)
The research (The relation of family with constructing the capability of the students - the research is field conducted by researcher on Sulaimani High Schools). It consists of theoretical and technical, which showcases and uses the issues, significance, goals, scopes and surveys as fundamental tools to collect the data, society among High Schools of Sulaimani province. The Purposive Sampling. The number of schools and students that included, (114) which classifies into (106) public schools, (8) private schools, with total of (44568) students. The aim of the research is to show the role of family in creating students’ capabilities in regard to social relations, learning, self confidence and decision-making skills. پێشه‌كى: